New cardo bisphenol monomer containing pendant azido group and the resulting aromatic polyesters - Maher, Deepak M.; Nagane, Samadhan S.; Jadhav, Uday A.; Salunkhe, Pravin H.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
Expanding on our strategy to synthesize aromatic step-growth polymers containing pendant clickable azido groups via functional monomer approach, we have now designed and synthesized a new cardo bisphenol, viz., 2-(2-azidoethyl)-3, 3-bis(4-hydroxyphenyl) isoindolin-1-one (PPH-N-3). PPH-N-3 was conveniently synthesized starting from commercially available phenolphthalein by a three-step route in an overall yield of 65% using simple organic transformations. Aromatic (co)polyesters bearing pendant azido groups were synthesized by low-temperature solution polycondensation of PPH-N-3 or different molar ratios of PPH-N-3 and bisphenol-A (BPA) with aromatic diacid chlorides in dry dichloromethane in the presence of triethylamine (TEA) as a base. The formation of medium to reasonably high-molecular-weight (co)polyesters was evidenced from intrinsic viscosity and number-average molecular-weight measurements that were in the range 0.52-0.85 dL/g and 16,700-28,200, respectively. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polyesters. (Co)polyesters were characterized using FTIR, H-1 NMR, C-13 NMR spectroscopy, XRD, and TGA. The thermal curing reaction of (co)polyesters involving decomposition of azido groups was studied by DSC analysis. The chemical modification of a representative copolyester containing pendant azido groups was carried out quantitatively using catalyst-free azide-maleimide cycloaddition reaction with two maleimides, namely, N-methylmaleimide and N-hexylmaleimide. (c) 2019 Wiley Periodicals, Inc.
Keywords: aromatic (co)polyester; azido group; cardo bisphenol; Chemical modification

Thermally crosslinkable and chemically modifiable aromatic polyesters possessing pendant propargyloxy groups - Verma, Savita; Maher, Deepak M.; Nagane, Samadhan S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
New aromatic (co)polyesters containing pendant propargyloxy groups were synthesized by phase transfer-catalyzed interfacial polycondensation of 5-(propargyloxy)isophthaloyl chloride (P-IPC) and various compositions of P-IPC and isophthaloyl chloride with bisphenol A. FTIR and NMR spectroscopic data, respectively, revealed successful incorporation of pendant propargyloxy groups into (co)polyesters and formation of (co)polyesters with desired compositions. (Co)polyesters exhibited good solubility in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran and could be cast into transparent, flexible, and tough films from chloroform solution. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.77-1.33 dL/g and 43,600-118,000 g/mol, respectively, indicating the achievement of reasonably high-molecular weights. The 10% weight loss temperatures of (co)polyesters were in the range 390-420 degrees C, demonstrating their good thermal stability. (Co)polyesters exhibited T-g in the range 146-170 degrees C and T-g values decreased with increase in mol % incorporation of P-IPC. The study of non-isothermal curing by DSC indicated thermal crosslinking of (co)polyesters via propargyloxy groups. The utility of pendant propargyloxy group was demonstrated by post-modification of the selected copolyester with 1-(4-azidobutyl)pyrene, 9-(azidomethyl)anthracene, and azido-terminated poly(ethyleneglycol) monomethyl ether via copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction. FTIR and H-1 NMR spectra confirmed that click reaction was quantitative. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 588-597
Keywords: Click chemistry; crosslinking; modification; polyesters; propargyloxy; step-growth polymerization

Pendant propargyloxy-functionalized aromatic (co)polycarbonates: synthesis, thermal crosslinking and chemical modification - Nagane, Samadhan S.; Maher, Deepak M.; Verma, Savita; Talanikar, Aniket A.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2022)
A bisphenol monomer bearing pendant propargyloxy group viz, 1, 1-bis (4-hydoxyphenyl)-1-(4 `-propargyloxyphenyl) ethane (BPP) was synthesized starting from commercially available 1, 1, 1-tris (4-hydroxyphenyl) ethane (THPE) by mono O-propargylation reaction using propargyl bromide. A new series of pendant propargyloxy-functionalized aromatic (co)polycarbonates was synthesized by low-temperature solution polycondensation of BPP or different molar ratios of BPP and bisphenol-A with triphosgene in dichloromethane in the presence of triethylamine. The formation of reasonably high molecular weight (co)polycarbonates was confirmed by inherent viscosity (0.52-0.83 dL/g) and gel permeation chromatography (M-n 37,000-69,800 g/mol, polystyrene standards) measurements. C-13 NMR spectral studies supported formation of random copolycarbonates in copolymerization of BPP and BPA with triphosgene. The 10% weight loss temperature (T-10) values of (co)polycarbonates, determined by thermogravimetric analysis under nitrogen atmosphere, were in the range 427-438 degrees C indicating their good thermal stability. The glass transition temperature (T-g) values of (co)polycarbonates were observed in the range 147-152 degrees C. The crosslinking ability of (co)polycarbonates involving pendant propargyloxy groups leading to formation of networked structure was evaluated via non-isothermal curing studies by DSC. As a proof-of-concept, the post-modification of a representative polycarbonate bearing pendant propargyloxy groups with 1-octane thiol as a model compound via thiol-yne click reaction was briefly studied.
Keywords: Aromatic polycarbonate; Chemical modification; propargyloxy groups; thermal crosslinking; thiol-yne click reaction